2022
DOI: 10.3390/foods11233793
|View full text |Cite
|
Sign up to set email alerts
|

Methylation, Hydroxylation, Glycosylation and Acylation Affect the Transport of Wine Anthocyanins in Caco-2 Cells

Abstract: Anthocyanins are substances with multiple physiological activities widely present in red wine, but the influence of structure (methylation, hydroxylation, acylation, glycosylation) on the transport remains ill-defined. In the present study, Caco-2 monolayers were used as an in vitro model of the absorptive intestinal epithelium to transport different types of anthocyanin samples. Results showed that both methylation and acetylation promote the level of transport. Monoglycoside standard exhibited higher transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Both passive diffusion or active transporters (sodium-dependent glucose transporter 1 (SGLT1) and glucose transporter 2 (GLUT2)) transport anthocyanins and their degradation products through intestinal epithelial cells, with their absorption rate depending on their specific structure . Besides that, anthocyanins’ transport across the gastrointestinal barriers occurs in a time- and concentration-dependent manner . Rather than being absorbed in the upper small intestine, the majority of anthocyanins pass to the colon, , where they are metabolized into a variety of low-molecular-weight catabolites by bacteria from the intestinal microbiota, with the main metabolic processes including the cleavage of glycoside bonds, hydrogenation, methylation, hydroxylation, and decomposition. ,, A human intervention study (healthy + ileostomy probands) has confirmed that the colon is a vital organ for absorbing biologically active ingredients including anthocyanins as well as their degradation derivatives .…”
Section: Basic Information About Anthocyaninsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both passive diffusion or active transporters (sodium-dependent glucose transporter 1 (SGLT1) and glucose transporter 2 (GLUT2)) transport anthocyanins and their degradation products through intestinal epithelial cells, with their absorption rate depending on their specific structure . Besides that, anthocyanins’ transport across the gastrointestinal barriers occurs in a time- and concentration-dependent manner . Rather than being absorbed in the upper small intestine, the majority of anthocyanins pass to the colon, , where they are metabolized into a variety of low-molecular-weight catabolites by bacteria from the intestinal microbiota, with the main metabolic processes including the cleavage of glycoside bonds, hydrogenation, methylation, hydroxylation, and decomposition. ,, A human intervention study (healthy + ileostomy probands) has confirmed that the colon is a vital organ for absorbing biologically active ingredients including anthocyanins as well as their degradation derivatives .…”
Section: Basic Information About Anthocyaninsmentioning
confidence: 99%
“…As an important subfamily of flavonoids, anthocyanins consist of a common tricyclic structure with two benzyl rings (A and B) and one heterocyclic ring (C) (Figure ) , and usually with 2 or 3 substituents, containing a sugar group and frequently an organic acid group , More than 1000 anthocyanins have been found in plants . Anthocyanins occur in nature as anthocyanidin glycosides, which are considered more stable than anthocyanidins .…”
Section: Basic Information About Anthocyaninsmentioning
confidence: 99%